2019
DOI: 10.1590/2236-8906-05/2018
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and quality of seeds and plantlets of Eugenia uniflora L.

Abstract: This work evaluated the effect of pollination on the quality of seeds and plantlets of Eugenia uniflora L., as well as on the regenerative capacity of the seeds. Twelve individuals were monitored for their phenology and their floral visitors. Recently-opened flowers were subjected to self-pollination (SP), cross-pollination (CP) and natural pollination/control (C) treatments. The seeds obtained were evaluated for their germination and the resulting seedlings were transferred to a greenhouse and evaluated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
1
0
2
Order By: Relevance
“…The current study showed no significant difference of seed germination of okra among treatments. Results of our research also supported several previous studies on Eugenia uniflora (Fidalgo et al, 2019). Similarly, the pollination of okra by stingless bees was not significantly different from the control (Sihag, 1986).…”
Section: Pod and Seed Yieldssupporting
confidence: 92%
“…The current study showed no significant difference of seed germination of okra among treatments. Results of our research also supported several previous studies on Eugenia uniflora (Fidalgo et al, 2019). Similarly, the pollination of okra by stingless bees was not significantly different from the control (Sihag, 1986).…”
Section: Pod and Seed Yieldssupporting
confidence: 92%
“…The germination may be stimulated by micro-climate changes in relation to disturbance, such as sunlight (due to the opening of forest canopy), moisture regimes, temperature, as well as changes in the ecological community such as predators and dispersers (Kallow et al 2020). The germination rate is also affected by genetic factors, pollination rate, population size, pollinators availability and environmental conditions during fruit ripening (Kaiser et al 2016;Fidalgo et al 2019).…”
Section: Seed Germination Of M Acuminata Var Flavamentioning
confidence: 99%
“…For instance, evolutionary processes and historical events act as filters on global scales, while the selection of habitats and the dispersion capacity of species act on regional scales to determine community composition [2]. On a local scale, abiotic factors (such as precipitation, temperature, humidity, evapotranspiration, soil characteristics, and light availability) and biotic factors (biological interactions) are the main filters [2][3][4]. Regarding these biotic factors, pollination is an important mutualistic interaction, since many plant species rely on pollinators to produce fruits and seeds to establish and maintain viable populations in the environment [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%